Carbamylated vimentin represents a relevant autoantigen in Latin American (Cuban) rheumatoid arthritis patients - Martínez, Goitybell (Rheumatol Int, 2016)
Smoking produces substances that activate proinflammatory, prothrombotic and vasoconstrictive mediators via posttranslational carbamylation of proteins. As a new consequence of carbamylation, induction of anti-carbamylated autoantibodies were observed in rheumatoid arthritis (RA) patients, sometimes prior to onset of the disease. The overall aim of this study was to characterize the reactivity of different isotypes of autoantibodies against carbamylated antigens of vimentin in relation to established rheumatoid factor (RF), anti-citrullinated protein antibodies (ACPA) and markers of disease activity in a so far largely uncharacterized population of Latin American (Cuban) patients with RA. Antigenic properties of carbamylated vimentin as well as vimentin peptides were analyzed in 101 patients with RA, 50 disease controls and 51 healthy controls. The diagnostic performance was compared with established commercial ELISA rheumatoid factor, anti-cyclic citrullinated peptide antibodies of second generation (anti-CCP2) and anti-mutated citrullinated vimentin (anti-MCV) antibodies. Prevalence of anti-MCV IgG (86 %), anti-carbamylated vimentin (carbVIM) IgG (77 %) and anti-carbamylated MCV (carbMCV) IgG antibodies (65 %) was higher than the classical RF IgM (60 %) and anti-CCP2 IgG (52 %) in this RA cohort. Of note, smoking status was associated with positive IgG antibody reactivity against CCP2 in 75.0 % and against MCV in 90 % of patients. Furthermore, IgM antibody response against carbMCV and carbVIM was observed in 80 and 90.0 % of smokers, respectively. Due to a high sensitivity of the IgM antibody isotype of anti-carbVIM of 85.2 %, the combination of ACPA with anti-carbVIM IgM provided the best diagnostic performance so far achieved in a RA cohort of this ethnic origin. We demonstrate a high prevalence of anti-carbVIM antibodies and correlation with smoking in Latin American (Cuban) RA patients. Anti-carbVIM IgM represents an useful marker in ACPA-negative patients and, in combination with ACPA IgG assays, optimizes the strategy for autoantibody testing. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00296-016-3472-9) contains supplementary material, which is available to authorized users.